Reflections on Ibn Jinni's Thought : Analysis of words and meanings in Arabic Semantics - Muid, Abdul; Mabrurrosi, Mabrurrosi (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2022)
Here is no doubt that Ibn Jinni is one of the popular Arab linguistic figures. From various references, it is said that Ibn Jinni is an expert in the science of nahwu (Syntax). One of the monumental works that he gave birth to is Al-Khashais. Moreover, several other works support Ibn Jinni's linguistic thinking. One of the interesting studies to explore is word and meaning, which are in the scope of the macro language and cannot be separated from Arabic linguistic studies. Besides the relationship between words and meaning, according to Ibn Jinni, the two elements of language were developed as a means of communication, both spoken and written. Therefore, the study of words and its meaning needs to be understood from all aspects of language and the socio-cultural context in general. words and meaning are the subjects of multi-perspective linguistic research giving rise to linguistic studies. Linguistic reflection on lafazh and its meaning is important as a theoretical basis for understanding Arabic texts and for the development of learning Dalalah for Arab scholars or scholars.